ACHIEVEMENT OF EQUIVALENCE TROUGH TRANSLATION OF OIL AND GAS TERMINOLOGY BASED ON TECHNICAL STANDARDS - Muchka, М. Z.; Hreliuk, Yu. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The characteristic features of translation oil and gas terminology based on the technical standard are studicol in the article. The problems of achieving equivalence by means of translation transformations are generalized.